Complete 1H and 13C NMR spectral assignment of N‐aralkylsulfonamides, N‐sulfonyl‐1,2,3,4‐tetrahydroisoquinolines and N‐sulfonyl‐2,3,4,5‐tetrahydro‐1H‐2‐benzazepines. Conformational analysis of N‐[((3′,4′‐dichlorophenyl)methyl)sulfonyl]‐3‐methyl‐2,3,4,5‐tetrahydro‐1H‐2‐benzazepin - Jios, Jorge Luis (2005)
The complete and unambiguous assignment of the 1H NMR and 13C NMR spectra of 26 N-aralkylsulfonamides, N-sulfonyl-1,2,3,4-tetrahydroisoquinolines and N-sulfonylbenz[c]azepines was performed on the basis of APT, DEPT, homonuclear (gs-COSY) and 1H-detected heteronuclear one-bond (gs-HMQC) and long-range (gsHMBC) correlation experiments. The methylated 2,3,4,5- tetrahydro-1H-2-benzazepine derivative 26 adopts a chair conformation as determined by 1H- 1H coupling analysis and g-gauche effects. This is supported by a single-crystal X-ray structure analysis.